The Social Skills of Students in the Pandemic Period (The Case Study in SMAN 1 Kedunggalar, Ngawi District, East Java, Indonesia) - Prima Retnaning Mareta; Akhmad Arif M; Susanto Susanto (BIRCU, 2021)
The increasingly prolonged pandemic period and its unclear ending have disrupted all human activities, one of which is learning activities in school. After the physical distancing policy is implemented, student-learning activities are carried out at home. This results in a decrease in the affective skills of students. Besides, the teachers also experience limitations in monitoring students’ affective behavior. Hence, this study's goal is to determine the extent to which students' social skills during the pandemic period. The research subjects were students of Kedunggalar 1 Senior High School (SMA Negeri 1 Kedunggalar), Ngawi Regency, with 76 students as respondents who were randomly selected from various classes, majors, and gender. This research was a qualitative descriptive study. Data collection techniques used questionnaires. Data analysis in this study referred to an interactive analysis model consisting of the stages of data reduction, data presentation, and data verification. Based on the results of this research, it can be seen how the attitude of students' social skills is during the pandemic.